CURBING THE FLOODING MENACE IN ZAMFARA STATE NIGERIA: A CASE STUDY OF THE GUSAU BARRAGE BREAKAGE BY - E, Obi Lawrence (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
Gusau Barrage is a suitable water project which can be employed in curbing flooding menace inZamfara State. The breakage of the Barrage resulted to a monumental flooding incidence in2006. This breakage of the barrage was studied through visits and available documents andliterature. The research targeted on how the experience of this incidence can be applied ineliminating future occurrences of flooding in the state. The research findings revealed that nonapplicationof the safety devices, poor elevation of the barrage over the highlands, high intensityof rainfall and non-desiltation of the barrage sections resulted in the collapse of the barrage. Thecollapse of the Barrage resulted in the flooding. This research, therefore, is of the view thatfuture flooding in Zamfara State can be effectively curbed if the barrage is well managed; itshydraulic head raised, the desilting of the river and the introduction of other uses of the waterimpoundment.